EXPEDIENCE OF APPLICATION OF STERICALLY COMPLICATED ACENAPHTHENE COMPOUNDS IN THE COMPOSITION OF ANTI-CORROSION COMPOSITION - DOROSHENKO, TATYANA; КАCHALOVA NATALIYA (Technologies and Engineering, 2022)
Goal. Synthesis and study of the effect of the inhibitory component – sterically complicated acenaphthene compounds – on the effectiveness of the protective composition to prevent corrosion of metal products during the period of temporary preservation. Method. Coke-chemical acenaphthylene was isolated from the absorbing and anthracene fractions of coal tar, the bromination of which led to 1,2-dibromocenaphthene. Subsequent alkylation of azine bases with 1,2-dibromacenaphthene yielded a number of sterically complex acenaphthene compounds. In the conditions of simulation aggressiveness of NSS environment the influence of synthesized additives on efficiency of anticorrosive composition is investigated (ISO 9227:2017). Research methods: chromatography, synthesis, elemental analysis, IR spectroscopy, corrosion tests. Results. On the basis of low-demand, available and inexpensive components of coke production, a number of substances with high anti-corrosion properties were synthesized – Quaternary azine salts with acenaphthene fragment. It was determined that the greatest resistance to the destructive effects of corrosive NSS environment according to the results of accelerated atmospheric corrosion tests was demonstrated by a composite coating containing an inhibitory additive – 1-(2-bromo-1,2-dihydroacenaphthylen-1-yl) quinoline bromide. The dominant role of the structure of the inhibitory additive on the manifestation of anticorrosive properties of the protective composition is shown. The influence of the ratio of components of paints and varnishes on their technological and anti-corrosion properties has been studied. The obtained results allow to create a new formulation of the domestic competitive protective composition to prevent corrosion of the metal for the period of temporary preservation. Scientific novelty. The role of 1,2-dibromacenaphthene as a promising alkylating agent in the synthesis of inhibitory additives - sterically complicated acenaphthene compounds has been determined. Practical significance. The optimal content of inhibitory components – Quaternary azine salts with acenaphthene fragment – for the development of a formulation of an effective anti-corrosion composition for the period of temporary preservation of metal products.